Analyzing The Factors Shaping Coriolanus Snow's Ambition in “The Ballad of Songbirds and Snakes” Novel by Suzanne Collins - Abdullah, Reflan; Balango, Mery; Katili, Adriansyah A. (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to analyze Coriolanus Snow's ambition and the factors that shape it in Suzanne Collins' "The Ballad of Songbirds and Snakes." Utilizing a social psychology approach grounded in Bronfenbrenner's Ecological Theory, this research explores how the interaction between Snow's personal characteristics and the Capitol's social, cultural, political, and economic environment influences the development of his ambition. Through a descriptive-qualitative analysis of the novel's text, the study reveals that internal factors, such as personality traits, significantly shape Snow's ambition. Additionally, external factors—including cultural norms, school policies, government directives, historical events, and interactions with family, friends, and mentors within the mesosystem—exert a complex and interrelated influence on his behavior and life goals. The findings indicate that Coriolanus Snow's ambition to restore his family's glory by pursuing wealth, power, and influence is shaped by the dynamic interplay of internal and external factors. This study highlights the importance of considering both types of factors to comprehensively understand the development of an individual's ambition.